A Review: Investigation of Augmented Reality – BIM Benefits in Design Process in Aec Industry - AL-Dhaimesh, Sadeer Hel; Taib, Nooriati (Informatica, 2023)
The industry of Architecture, Engineering, Construction, has long been known as dynamic and complicated. A Growing demands on building projects in areas such as safety, energy, time, and financial management have driven the sector toward new tools and processes, including more effective utilization digital technology, in recent years. Building Information Modelling (BIM) is gradually establishing itself as a core technique among the several accessible digital solutions, with its practices and technologies being progressively used. The existing barriers to BIM adoption, on the other hand, give an opportunity for the creation of supporting technologies. The current article examines Augmented Reality (AR) as a tool in this regard. A comprehensive study was carried out to investigate existing research in the domain of BIM-based AR, revealing insight on its integration in the AEC industry. PRISMA-P is the reviewing approach that was adopted. A total of 79 articles were chosen for the study from a sample of 120 articles. This assessment demonstrates that AR implementation is far from complete, with various constraints such as connectivity and localization issues, a lack of non-geometric information, and other difficulties in employing AR techniques on the building site. The motivation of this paper comes from the lack of attention in augmented reality through BIM among previous studies adding that previous theorist included augmented reality adoption alone. This paper distinguished by its content for AR application into BIM from conceptual stage, architecture stage, construction stage and maintenance stage.